Gender-related stigma toward individuals with a history of sexual or physical violence in childhood - Theresia Rechenberg; Toni Fleischer; Christian Sander; Georg Schomerus (BMC, 2024)
Abstract Background Stigma is a key barrier to disclosing traumatic experiences of violence in childhood with adverse consequences for help-seeking behaviour. Disclosing behavior differs by gender and the form of violence experienced. However, there is a lack of comprehensive studies that address societal perceptions of males and females with a history of sexual or physical violence in childhood. Therefore, our aim is to focus on the impact of gender on the perception of individuals who experienced sexual or physical violence in childhood. Methods We conducted a study on a representative sample of the German general population in terms of age and gender. Participants were randomly assigned to brief case vignettes addressing sexual or physical violence in childhood. Analyses base on a sample of n = 659 individuals (50.1% female). Stigma was assessed through examining respondents' readiness to address specific traumas in conversation and respondents' attitudes toward the individuals in the vignettes. Mann-Whitney U tests were applied to check for differences between female and male victims and survivors as well as female and male respondents. Results Our results reveal that male victims and survivors face higher negative stereotypes (harm, unpredictability) and evoke communication barriers more often when compared to female victims and survivors, especially in male respondents. Sexual violence is associated with more distinct gender differences than physical violence. Conclusions Findings reflect greater stigma toward male victims and survivors of sexual violence than female ones. Men had a greater tendency to stigmatize - especially toward their same-gender peers. Socially ingrained gender roles may act as a basis for different communication cultures and the notion of victim-perpetrator constellations in which males are not envisaged as victims.